IMPULSIVE BUYING BEHAVIOUR DALAM PERSPEKTIF EKONOMI ISLAM - Nur Rahmah; Munadi Idris (Jurnal Ekonomi Bisnis Syariah, 2018)
Impulsive buying behavior is part of consumptive behavior that makes purchases without planning (spontaneous) driven by the human desire that becomes unlimited desire. In the perspective of Islamic economics, consumption is allowed as long as it has benefits for consumers with attention to the good and bad as well as the halal and haramnya a product consumed. This study aims to determine the consumption in Islamic economics, consumption behavior in Islamic economics and Impulsive Buying Behavior in Islamic Economic Perspective. Data collection is literature review or literature, with normative descriptive data analysis technique to study about Islamic economic theory related to impulsive buying behavior. The results of the analysis and discussion that impulsive buying behavior in Islamic economics is based on the buying behavior of mashlahah desire to fulfill the desire of needs that bring benefit and blessing to the consumer. Keyword: Impulsive buying behavior, Consumption, Mashlahah